2010
DOI: 10.4081/ija.2010.3
|View full text |Cite
|
Sign up to set email alerts
|

The Biochar Option to Improve Plant Yields: First Results From Some Field and Pot Experiments in Italy

Abstract: The pyrolysis conversion of agricultural residues into biochar and its incorporation in agricultural soil, avoids CO 2 emissions providing a safe long-term soil carbon sequestration. Furthermore, biochar application to soil seems to increase nutrient stocks in the rooting zone, to reduce nutrient leaching and to improve crop yields. This study reports some preliminary results obtained using biochar in two typical Italian agricultural crops. Two field experiments were made on durum wheat (Triticum durum L.) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
69
0
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 33 publications
11
69
0
11
Order By: Relevance
“…The yield rose to 300% when cattle urine was added to this BC before soil application. Similar yield increases have been reported by Baronti et al (2010) in maize, in Chenopodium, and Alburquerque et al (2013) in wheat when BC was combined with either organic residues/compost or mineral fertiliser, and indicate that wood BC may raise nutrient use efficiency when added to organic/inorganic fertiliser/crop residues.…”
Section: Interaction With Organic and Inorganic Fertiliserssupporting
confidence: 63%
See 3 more Smart Citations
“…The yield rose to 300% when cattle urine was added to this BC before soil application. Similar yield increases have been reported by Baronti et al (2010) in maize, in Chenopodium, and Alburquerque et al (2013) in wheat when BC was combined with either organic residues/compost or mineral fertiliser, and indicate that wood BC may raise nutrient use efficiency when added to organic/inorganic fertiliser/crop residues.…”
Section: Interaction With Organic and Inorganic Fertiliserssupporting
confidence: 63%
“…Many recent studies have reported increased crop yield (Subedi et al, 2016a;Vaccari et al, 2011;Usman et al, 2016;Kammann et al, 2012;Baronti et al, 2010;Uzoma et al, 2011;Houben et al, 2013;Genesio et al, 2015;Cornelissen et al, 2013;De La Rosa et al, 2014;Fox et al, 2014;Gregory et al, 2014;Lin et al, 2015;Schmidt et al, 2015;Butnan et al, 2015;Laghari et al, 2015;Mandal et al, 2016). Others have reported no yield effect (Cornelissen et al, 2013;Uzoma et al, 2011;Nelissen et al, 2015;Subedi et al, 2016aSubedi et al, , 2016bNielsen et al, 2014;Tammeorg et al, 2014;Suddick and Six, 2013;Schmidt et al, 2014;Bass et al, 2016).…”
Section: Biochar Effects On Crop Productivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Results from Baronti et al (2010) showed that a 1.7% coppiced woodland-biochar application to soil caused the maximum dry matter production in potted perennial ryegrass, due to an overall amelioration of growth condition, but above this threshold a general reduction of biomass was observed, probably because of changes in some soil properties. Lower performances of Euphorbia × lomi grown in the substrate containing 100% biochar are probably due to the deterioration of chemical (alkaline pH, higher EC and Na) and physical conditions (lower water content and its availability for plants, excessive air content); this response is in line with that from Rondon et al (2007) who observed that the addition of high rate of Eucalyptus wood biochar to a poor soil in a pot experiment resulted in a decrease of crop yield probably due to a micronutrient deficiency induced by increasing soil pH.…”
Section: Plant Growth and Biomass Yieldmentioning
confidence: 99%